BATASAN HUBUNGAN BAGI LELAKI DAN WANITA PASCA KHIṬBAH PERSPEKTIF MADZHAB SYAFI’I - Kanzun Bairuha (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2023)
The sermon is the first step in a marriage which has the aim and purpose of ensuring that each party knows the partner who will be their life partner. Couples who are still in the khitbah period still have the status of other people and must protect their relationship with their partner from things that are not permitted by Islamic law. The two of them cannot have a relationship like husband and wife because they are not married. This research was conducted using a type of library research, namely research that uses libraries as a research source. In the book Fathul Wahhab it is explained that men can look at women or vice versa when they both want to get married with restrictions other than looking at their private parts when praying. Both of them can see each other repeatedly and within the period until the marriage contract without any definite limits. In the books Fathul Mu'in and Fathul Qorib it is also explained this way. The two of them are also allowed to chat and chat with each other as long as this does not cause slander, so the woman must have a mahram when she wants to meet. What is prohibited is seclusion, or being alone without a woman's mahram because this allows slander to occur. Apart from that, both of them are also not allowed to touch or touch any part of the body, even though they can see parts such as the face or palms of the hands.